Use of bandage contact lenses in dogs with spontaneous chronic corneal epithelial defect after interventional treatment - Batchelor, Charlie (Veterinary Evidence, 2026)
PICO Question In dogs with spontaneous chronic corneal epithelial defects (SCCEDs), does the use of a bandage contact lens (BCL) after interventional treatment compared to treatment alone decrease the time to clinical resolution? Clinical bottom line Category of research Treatment. Number and type of study designs reviewed Three studies were reviewed, one of which was a prospective non-randomised observational study, one was a case control study, and one was a prospective randomised controlled trial. Strength of evidence Strong. Outcomes reported All studies demonstrated appropriate healing, with three studies showing a shorter corneal healing time with the use of a bandage contact lens. No studies demonstrated a longer or similar healing time with use of a bandage contact lens. Conclusion In cases of canine SCCEDs, application of a bandage contact lens after interventional treatment shortens corneal healing time.